Innate attractant for long‐tongued bumblebee, Bombus diversus diversus in floral scent of bumblebee‐pollinated epiparasitic plant, Monotropastrum humile (Ericaceae). Issue 4 (16th February 2014) - Kubo, Ryohei; Ono, Masato
Abstract The epiparasitic plant Monotropastrum humile (D. Don) Hara is pollinated by workers of the long‐tongued bumblebee, Bombus diversus diversus (Smith). The interaction between the floral scents of this plant and bumblebee was investigated using electrophysiological and behavioral techniques. Three components (linalool, α‐terpineol and geraniol) elicited strong responses in antennae from B. d. diversus workers and are innate attractants, suggesting floral scents play an important role in attracting these pollinators and successful pollination.